HARIMAU DALAM KARYA RUGMAKING DENGAN TEKNIK GIORDES DAN RENDA - Sherly Sri Yultra Drs. Erwin A, M.Sn., Drs. Erfahmi, M.Sn. (Universitas Negeri Padang, 2017)
The goal is to create or visualize objects craft textiles with a tiger through the work rugmaking with giordes techniques and lace. This thesis was made through five stages, namely preparation phase (exploration), phase penetepan ideas (elaboration), the synthesis, the realization of the concept and stages of completion. The work achieved by the title of neglect, loneliness, lying, excellence, just us, compassion, and entangled. The title is taken from a tiger very poor condition due to poaching. This work is made manually, producing work that is unique and has artistic value that can be used to beautify the room. Hopefully these ideas and techniques can be developed by writers or other writers in the future.Kata kunci: Harimau, Seni Kriya, Kriya tekstil, Rugmaking, teknik giordes dan renda.